2011
DOI: 10.3389/fnhum.2011.00117
|View full text |Cite
|
Sign up to set email alerts
|

What is Grouping during Binocular Rivalry?

Abstract: During binocular rivalry, perception alternates between dissimilar images presented dichoptically. Although perception during rivalry is believed to originate from competition at a local level, different rivalry zones are not independent: rival targets that are spaced apart but have similar features tend to be dominant at the same time. We investigated grouping of spatially separated rival targets presented to the same or to different eyes and presented in the same or in different hemifields. We found eye-of-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
44
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 38 publications
(54 reference statements)
10
44
2
Order By: Relevance
“…solid evidence for both kinds of contributions (32,(35)(36)(37)(38), and binocular rivalry is widely viewed as the culmination of neural events distributed over multiple stages of processing comprising feedforward and feedback connections (4). What the present results indicate is that during stimulus rivalry, just like during binocular rivalry, those stages include very early ones in which interocular competition transpires.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…solid evidence for both kinds of contributions (32,(35)(36)(37)(38), and binocular rivalry is widely viewed as the culmination of neural events distributed over multiple stages of processing comprising feedforward and feedback connections (4). What the present results indicate is that during stimulus rivalry, just like during binocular rivalry, those stages include very early ones in which interocular competition transpires.…”
Section: Discussionsupporting
confidence: 53%
“…In our model, this situation arises through a difference between the two components in both their maximum strength and their time scale of decay during stimulus absence. Although it is not straightforward to arrive at estimates of these characteristics from empirical work, there is some evidence that between-eye iso-orientation suppression is indeed the stronger of the two (25,32). Regarding the crossover in strength for interrupted stimuli, an intriguing possibility is suggested by work that points to a type of within-eye inhibition that is strongest right after stimulus onset and for rapidly changing stimuli but becomes weaker during sustained stimulation (22,33).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a greater sensitivity to expansion. Although this result is not in line with our assumption, it is known that mutual interactions related to the relative feature content of the competing images affect binocular rivalry (Stuit, Cass, Paffen, & Alais, 2009;Stuit, Paffen, van der Smagt, & Verstraten, 2011). Such interactions could in turn affect the relative sensitivity to expanding and contracting optic flow, complicating the interpretation of the data.…”
Section: Introductioncontrasting
confidence: 70%
“…Our previous results demonstrated that image-based grouping can essentially be reduced to zero, while eye-based grouping remains strong when grating stimuli are used [17]. Specifically, in that study, we found an increase in dominance durations based image-content for cardinally oriented gratings, but not for diagonally oriented gratings.…”
Section: Discussionmentioning
confidence: 45%